2012
DOI: 10.1149/2.004205jes
|View full text |Cite
|
Sign up to set email alerts
|

Direct Simulation of Liquid Water Dynamics in the Gas Channel of a Polymer Electrolyte Fuel Cell

Abstract: For better water management in gas channels (GCs) of polymer electrolyte fuel cells (PEFCs), a profound understanding of the liquid water dynamics is needed. In this study, we propose a novel geometrical setup to conduct a series of direct simulations of the liquid water dynamics in a GC. The conducting pathways in the gas diffusion layer (GDL) are simplified by three cylindrical pipes connected to a liquid water reservoir representing the catalyst layer (CL). The droplet dynamics, corner film dynamics, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Qin et al 29 studied the effect of the sidewall contact angle on the film flow at the GC corners by means of direct simulations. They concluded that larger contact angle of the hydrophilic sidewalls was beneficial to the film removal at the GC corners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qin et al 29 studied the effect of the sidewall contact angle on the film flow at the GC corners by means of direct simulations. They concluded that larger contact angle of the hydrophilic sidewalls was beneficial to the film removal at the GC corners.…”
Section: Resultsmentioning
confidence: 99%
“…This is a reasonable assumption under low gas flow rates. 8,9,29 Governing equations.- Fig. 3 depicts the assumed idealized liquid water distribution in the GC cross section, which is separated into film (including two symmetric parts) forming at the hydrophilic GC corners, as well as droplet sitting on the hydrophobic GDL surface (i.e.…”
Section: Physical Modelmentioning
confidence: 99%
“…In the literature, there have been many pore-scale numerical studies of liquid water transport in the GDL ([2, [16][17][18] many thereof) and gas channels (GCs) [19]. Recently, evaporation was also included in the pore-network modeling [2,20] for understating its role in water management.…”
Section: Introductionmentioning
confidence: 99%
“…This has stimulated many pore-scale numerical studies of the GDL over the past few years. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Several distinctive features of liquid water transport in the GDL make its pore-scale modeling extremely difficult. First, a small flow rate of liquid water, with a capillary number value of around 10 −8 , causes the modeling computationally expensive.…”
mentioning
confidence: 99%
“…But, the computational effort was extremely heavy. Compared to direct simulations, [29][30][31][32][33] the pore-network modeling has attracted more attention, [16][17][18][19][20][21][22][23][24][25][26][27][28] mainly because it is computationally cheap. The basic idea of a pore-network model is to first construct a pore network which can adequately represent the porous medium of interest; then, flow and transport are solved in the constructed network, usually with the help of some local rules.…”
mentioning
confidence: 99%